До проблеми сучасної методології: концептуальне поєднання феміністичної і психоаналітичної критики - Криворучко, Світлана; Krivoruchko, Svetlana (Східноєвропейський національний університет імені Лесі Українки, 2015)
Феміністична критика ззосереджується на проблемах тендерної сутності жінки. С. де Бовуар звернула увагу на художні образи жінок у літературі з точки зору «умовності» і «соціалізації», на підставі якої утворилося розрізнення «жіночого», «феміністського» і «фемінного» аспектів. Плідним є поєднання техніки С. де Бовуар із методом психіатра Дж.-Ш. Болєн, яка виокремлює три категорії богинь: 1) незаймані богині (Артеміда, Афіна, Гестія); 2) уразливі богині (Гера, Деметра, Персефона), 3) алхімічна богиня (Афродита). Слушно дослідити, як проявляються архетипи виокремлених богинь у художніх образах відповідно «фемінному», «феміністському» та «жіночому» концептам, що сприятиме проясненню специфіки притчевості у художніх творах письменників. Feminist criticism concentrates on f woman's image in literature where the form of socialization is being depicted on the level of probability of mimicry. The aim of feminist criticism is to research female images in male and female literature in order to estimate once more experience, overview literary canon, return from oblivion texts written by women. Special attention is paid to analysis of power relationship which demonstrates level of patriarchal influence in order to ruin them. In fiction images analysis they usually speculate over the difference between men and women with the object to understand whether it is biological essence or social construct. French feminism concentrates on problems of gender essence of a woman and determines it as existential. Simone de Beauvoir turned her attention to the fiction images of women in literature from the point of view of convention and socialization on the basis of which was formed the difference between female, feminist, feminine aspects. The guise of the other from the point of view of the author is psychological inhibition of a woman being deficient in the eyes of a man. S. de Beauvoir's technique together with psychiatrist Jean Shinoda Bolen's method is productive. The researcher identifies three categories of goddesses: 1) virgin goddesses (Artemis, Athena, Hestia); 2) sensitive goddesses (Hera, Demeter, Persephone); 3) alchemical goddess (Aphrodite). It is to the point to analyse how above mentioned goddesses' archetypes form themselves in fiction images according to feminine, feminist, female concepts which would help to clarify the specifications of parable in works of fiction.
То the Problem of Contemporary Methodology: Conceptual Combination of Feministic and Psychoanalytic Criticism
Keywords: феміністична школа; психоаналітичний підхід; feminist school; psychoanalytic approach